Carbohydrate Staple Food Modulates Gut Microbiota of Mongolians in China - Li, Jing; Hou, Qiangchuan; Zhang, Jiachao; Xu, Haiyan; Sun, Zhihong; Menghe, Bilige; Zhang, Heping (Frontiers in Microbiology, 2017)
Gut microbiota is a determining factor in human physiological functions and health. It is commonly accepted that diet has a major influence on the gut microbial community, however, the effects of diet is not fully understood. The typical Mongolian diet is characterized by high and frequent consumption of fermented dairy products and red meat, and low level of carbohydrates. In this study, the gut microbiota profile of 26 Mongolians whom consumed wheat, rice and oat as the sole carbohydrate staple food for a week each consecutively was determined. It was observed that changes in staple carbohydrate rapidly (within a week) altered gut microbial community structure and metabolic pathway of the subjects. Wheat and oat favored bifidobacteria (Bifidobacterium catenulatum, Bifodobacteriumbifidum, Bifidobacterium adolescentis); whereas rice suppressed bifidobacteria (Bifidobacterium longum, Bifidobacterium adolescentis) and wheat suppresses Lactobaciilus, Ruminococcus and Bacteroides. The study exhibited two gut microbial clustering patterns with the preference of fucosyllactose utilization linking to fucosidase genes (glycoside hydrolase family classifications: GH95 and GH29) encoded by Bifidobacterium, and xylan and arabinoxylan utilization linking to xylanase and arabinoxylanase genes encoded by Bacteroides. There was also a correlation between Lactobacillus ruminis and sialidase, as well as Butyrivibrio crossotus and xylanase/xylosidase. Meanwhile, a strong concordance was found between the gastrointestinal bacterial microbiome and the intestinal virome. Present research will contribute to understanding the impacts of the dietary carbohydrate on human gut microbiome, which will ultimately help understand relationships between dietary factor, microbial populations, and the health of global humans.